Flavonoids as GABAA receptor ligands: the whole story? - Wasowski C; Marder M (Dove Medical Press, 2012)
Cristina Wasowski, Mariel MarderInstituto de Química y Fisicoquímica Biológicas, Facultad de Farmacia y Bioquímica, Universidad de Buenos Aires, Buenos Aires, ArgentinaAbstract: Benzodiazepines are the most widely prescribed class of psychoactive drugs in current therapeutic use, despite the important unwanted side effects that they produce, such as sedation, myorelaxation, ataxia, amnesia, and ethanol and barbiturate potentiation and tolerance. They exert their therapeutic effects via binding to the benzodiazepine binding site of gamma-aminobutyric acid (GABA) type A receptors, and allosterically modulating the chloride flux through the ion channel complex. First isolated from plants used as tranquilizers in folkloric medicine, some natural flavonoids have been shown to possess selective affinity for the benzodiazepine binding site with a broad spectrum of central nervous system effects. Since the initial search for alternative benzodiazepine ligands amongst the flavonoids, a list of successful synthetic derivatives has been generated with enhanced activities. This review provides an update on research developments that have established the activity of natural and synthetic flavonoids on GABA type A receptors. Flavonoids are prominent drugs in the treatment of mental disorders, and can also be used as tools to study modulatory sites at GABA type A receptors and to develop GABA type A selective agents further.Keywords: flavonoids, GABA type A receptors, benzodiazepine binding site